A semi-internal combustion solid waste-based ceramic flat membrane and its preparation method
By using industrial solid waste such as fly ash and gasified slag to replace traditional alumina raw materials, and combining micron-scale alumina powder and high-temperature binder, ceramic flat films are prepared, which solves the problems of high cost of raw materials and large sintering energy consumption in the existing ceramic flat films, and achieves performance maintenance and cost reduction.
Patent Information
- Application Number
- CN202211736865.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-30
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2042-12-30
AI Technical Summary
In the existing preparation methods of ceramic flat films, the main raw material is alumina, which leads to high raw material costs and large sintering energy consumption, high product prices and insufficient market competitiveness.
Industrial solid waste such as fly ash and gasified slag are used as the main raw materials, combined with micron-scale alumina powder and high-temperature binder, and support is obtained by extrusion molding and sintering, spray molding and sintering to obtain a separate film layer, realizing the preparation of ceramic flat film.
It reduces raw material costs and sintering energy consumption, improves the market competitiveness of ceramic flat films, and has the performance comparable to that of ceramic flat films produced by traditional alumina raw materials.
Smart Images

Figure CN116328555B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a ceramic flat membrane and a preparation method thereof, in particular to a method for preparing a semi-internal combustion solid waste-based ceramic flat membrane using industrial solid waste as a main raw material, and belongs to the technical field of ceramic materials. Background Art
[0002] At present, there are many preparation methods of ceramic flat membranes disclosed in the prior art, but the main raw material is mostly alumina. For example, Chinese patent (CN108246119A) discloses a ceramic flat membrane for sewage treatment and its preparation method, the main raw materials of which are α-alumina, titanium oxide, and silicon oxide powder, and the sintering temperature reaches 1350°C; Chinese patent (CN109851328A) discloses a preparation process for a high-performance ceramic flat membrane support, which uses alumina powder at a ratio of up to 60-80%, and the sintering temperature reaches 1200-1500°C. Since the existing processes basically use pure commercial alumina to prepare ceramic flat membranes, on the one hand, the price of alumina itself is high, resulting in high raw material costs, and on the other hand, the sintering temperature required for sintering ceramic flat membranes with alumina is high, resulting in high sintering costs. It is precisely because the existing ceramic flat membranes have the disadvantages of high raw material costs and high sintering energy consumption that the product prices are high and the market competitiveness is insufficient, and it is urgent to solve the related problems. Summary of the invention
[0003] In view of the defects of the prior art, the first object of the present invention is to provide a solid waste-based ceramic flat membrane having excellent physical properties, such as a membrane pore size of 150 to 200 nm, a bending strength of 25 to 35 MPa, and a pure water flux of 0.7 to 1 m 3 / m 2 ·h, the pore size of the support is 1.5-2μm, the bending strength is 25-35MPa, and the pure water flux is 2-3m 3 / m 2 ·h, acid and alkali corrosion strength of 20-25MPa, which meets the application requirements of sewage treatment. In addition, it uses industrial solid waste as the main raw material for preparation, and has an absolute market competitive advantage in terms of cost.
[0004] The second object of the present invention is to provide a method for preparing a ceramic flat membrane. The preparation method makes full use of useful components such as silicon-aluminum components and metal oxides contained in solid wastes such as fly ash and gasification slag. Not only can high-performance ceramic flat membranes be obtained, but also the raw material cost is low and the sintering energy consumption is low, which is conducive to improving the market competitiveness of the product.
[0005] In order to achieve the above technical objectives, the present invention provides a semi-internal combustion solid waste-based ceramic flat membrane, which includes a support body and a separation membrane layer on its surface; the support body is obtained by extrusion molding and sintering of raw material I including silicon aluminum solid waste raw materials, micron-grade alumina powder and internal combustion agent; the separation membrane layer is obtained by spray molding and sintering of raw material II including fly ash, nano-grade alumina powder and high-temperature binder; the high-temperature binder contains borax, magnesium oxide, zinc oxide and albite.
[0006] The key to the present invention is to use silicon aluminum solid waste raw materials to partially replace the aluminum oxide raw materials in the ceramic flat membrane raw materials in the traditional process, and make full use of the silicon aluminum components and metal oxide components in these silicon aluminum solid waste raw materials. The silicon aluminum component is the main component for forming the ceramic phase, and the metal oxide can be used as a sintering flux component to improve the sintering effect. By optimizing the components, the performance of the ceramic flat membrane produced is equivalent to that of the ceramic flat membrane produced by the traditional aluminum oxide raw materials, thereby achieving the purpose of greatly reducing the cost of raw materials. At the same time, an internal combustion agent is introduced into the raw material of the support body, and the internal combustion agent can achieve internal combustion and external burning during the sintering process, significantly reducing the roasting energy consumption and effectively reducing the sintering cost. In addition, by using a special composite high-temperature binder, the melting temperature of the raw material can be greatly reduced, and the sintering temperature of the separation membrane layer can be significantly reduced, thereby preventing the secondary high-temperature sintering from affecting the pore structure of the support body, and can be better matched with the support body. The introduction of magnesium and zinc minerals can not only reduce the temperature, but also improve the alkali resistance of the membrane layer.
[0007] As a preferred solution, the fly ash is screened by its composition according to the origin of the raw material, preferably the main component of the fly ash is Al by weight. 2 O 3 The content is 30-50wt%, SiO 2 The content is 20-40wt%.
[0008] As a preferred solution, the high temperature binder comprises the following components by weight: 6-12 parts of borax, 2-5 parts of magnesium oxide, 4-8 parts of zinc oxide, and 20-35 parts of albite. The composite high temperature binder of the present invention can significantly reduce the melting temperature of the raw materials and significantly reduce the sintering temperature of the separation membrane layer. There is an obvious synergistic effect between the various components of the high-temperature binder. For example, borax and zinc oxide can react to form zinc borate as an excellent flux promoter. If the borax content is too high, it is easy to cause local melting and vitrification of the sample. If the borax content is too low, the zinc oxide will not react completely, and some zinc will be dissolved during the later use. Sodium feldspar can reduce the melting point of fly ash and the initial deformation temperature of the particles. When the content is too high, the acid resistance will be weakened, and when the content is reduced, the cooling effect will be weakened. The introduction of magnesium oxide can reduce the sintering problem by adjusting the alkalinity, and at the same time improve the alkali resistance of the separation membrane layer. By using a special high-temperature binder in the raw materials for preparing the separation membrane layer, on the one hand, it can prevent secondary high-temperature sintering from affecting the pore structure of the support body, and can better match the support body. On the other hand, the introduction of magnesium and zinc minerals can not only reduce the temperature, but also improve the alkali resistance of the membrane layer.
[0009] As a preferred solution, the raw material II contains the following components by weight: 30-40 parts of fly ash, 40-50 parts of nano-alumina powder, 3-8 parts of high-temperature binder, and 0.1-0.5 parts of dispersant. Fly ash and nano-alumina powder are used as the main raw materials, and the use of fly ash is mainly to replace part of the nano-alumina powder, and the silicon and aluminum sources in the fly ash are utilized to achieve the purpose of reducing costs. At the same time, the alkaline oxides in the fly ash can be used to adjust the alkalinity to reduce the sintering temperature of the film layer, prevent the excessive sintering temperature from affecting the performance of the support body, and the ratio of fly ash to nano-alumina powder is controlled within an appropriate range, which is conducive to the formation of mullite phase. However, when the fly ash content is high, after the film layer is sprayed, the film layer is prone to cracking and peeling during the drying process, and the fly ash particles added to the separation film layer are fine. Excessive addition will cause the sintering shrinkage to be inconsistent with the support body, resulting in sintering shrinkage and cracking of the film layer; and when the fly ash content is low, the sintering temperature of the film layer is high and cannot match the suitable temperature of the support body. If the proportion of high-temperature binder added is too small, the sintering temperature of the separation membrane layer will be too high, and the secondary high-temperature sintering will affect the pore structure of the support body. If the proportion of high-temperature binder added is too high, obvious pore blocking will occur, affecting the pore size control of the high-precision separation membrane layer and the average pore size.
[0010] As a more preferred solution, the particle size of the fly ash is 0.6-0.85 μm.
[0011] As a more preferred solution, the particle size of the nano-alumina powder is 0.6-0.7 μm.
[0012] As a more preferred solution, the particle size of the high temperature binder is 0.8-1 μm. These raw materials are controlled within a suitable particle size range, which is conducive to spray molding.
[0013] As a more preferred solution, the dispersant includes at least one of sodium metasilicate, sodium tripolyphosphate, sodium polyacrylate, and ammonium polyacrylate, which are conventional dispersants used in the preparation of ceramic flat membranes.
[0014] As a preferred solution, the raw material I comprises the following components by mass: 55-70 parts of silicon-aluminum solid waste raw materials, 5-15 parts of internal combustion agent, 7-15 parts of micron-grade alumina powder, 1-8 parts of plastic clay, 4-7 parts of pore-forming agent, 2-6 parts of temporary binder, 10-15 parts of low-melting glass powder, 3-7 parts of plasticizer, 0.5-2.5 parts of water reducer, 3-8 parts of lubricant, 1-2 parts of water retainer, and 0.2-1 parts of release agent. The key in the preparation process of the support body is that, on the one hand, aluminum silicon solid waste raw materials such as fly ash or gasified slag are used to replace part of the alumina raw materials in the traditional process, and by optimizing other components, a ceramic flat membrane with good performance can also be prepared. On the other hand, coal gangue with relatively high calorific value is added as an internal combustion agent, which can achieve internal combustion and external burning in the production process, significantly reducing roasting energy consumption and effectively reducing sintering costs. Generally speaking, if pure fly ash and other silicon-aluminum solid waste raw materials are used to prepare the support, the sintering shrinkage is large, the sintering temperature range is narrow, and the industrial production uniformity is poor. With an appropriate proportion of alumina, on the one hand, alumina particles can be used as rigid particles, which can play a pinning role and slow down the diffusion rate of materials between particles, thereby reducing sintering shrinkage. On the other hand, alumina can adjust the silicon-aluminum ratio of silicon-aluminum solid waste raw materials, which is conducive to obtaining mullite phase during sintering. However, if too much alumina is introduced, it will not only greatly increase the sintering temperature and reduce the sintering strength of the product, but also increase the cost of raw materials. In addition, the particles of silicon-aluminum solid waste raw materials such as fly ash have strong ridges and are difficult to plastically extrude. The introduction of plastic clay can enhance the viscosity of the mud, regulate the hardness and toughness of the mud, and then increase the plasticity. However, adding too much plastic clay will block the pores and reduce the porosity during the sintering process. In addition, the refractoriness of clay is generally higher than 1200℃, and too much addition will also increase the sintering temperature. Silica-alumina solid waste raw materials such as fly ash generally contain 5-10% residual carbon. During the mixing process, a hydrophobic film is easily formed on the surface of carbon particles. The introduction of water reducers can destroy this film, improve the wettability of liquids and particles, and enhance the performance of mud.
[0015] As a preferred solution, the silicon-aluminum solid waste raw material includes at least one of fly ash bottom ash, fly ash fly ash, gasification slag coarse slag, and gasification slag fine slag. As a more preferred solution, the silicon-aluminum solid waste raw material has a particle size of 5 to 6.5 μm, an aluminum content of ≥25wt%, and a silicon content of ≥35wt%.
[0016] As a preferred solution, the internal combustion agent includes at least one of coal gangue, coal slime, and high calorific value gasified slag. As a more preferred solution, the particle size of the internal combustion agent is 2-3 μm, and the received basis low calorific value is 600-1200 Kcal / kg. Further preferably, the received basis low calorific value of coal gangue and high calorific value gasified slag is 600-1000 Kcal / kg, and the received basis low calorific value of coal slime is 850-1200 kcal / kg. The internal combustion agent not only produces internal combustion during the sintering process, making the sintering more uniform, significantly reducing the roasting energy consumption, and effectively reducing the sintering cost, but also can provide a large amount of alkaline substances as a solvent, which can reduce the sintering temperature.
[0017] As a preferred solution, the low melting point glass powder includes at least one of silicate glass powder, borate glass powder and phosphate glass powder. As a more preferred solution, the softening and melting temperature of the low melting point glass powder is 800-1000°C. The low melting point glass powder can produce a small amount of liquid phase in the medium temperature range of 800-1000°C, which can bond and fuse the raw material particles to generate strength, promote the precipitation of mullite crystals, prevent the product from burning and cracking, and thus strengthen the sintering process of the green body.
[0018] As a preferred solution, the particle size of the micron-sized alumina powder is 5 to 6 μm.
[0019] As a preferred solution, the water reducer includes at least one of sodium humate, sodium carbonate, and tanning water reducer.
[0020] As a preferred solution, the plastic clay includes at least one of Suzhou clay, bentonite and ball clay.
[0021] As a preferred solution, the pore-forming agent includes at least one of ultrafine graphite particles, corn starch, and acrylic foam resin microspheres.
[0022] As a preferred solution, the temporary binder includes at least one of hydroxypropyl cellulose, sodium lignin sulfonate, and water glass. The temporary binder plays a bonding role at low temperatures, but will pyrolyze at high temperatures.
[0023] As a preferred solution, the plasticizer includes at least one of polyethylene glycol, PVA, and PVB.
[0024] As a preferred solution, the lubricant includes long-chain fatty acid methyl ester.
[0025] As a preferred solution, the water retaining agent includes glycerol.
[0026] As a preferred solution, the release agent includes at least one of type 400 stearic acid, oleic acid, and emulsified silicone oil.
[0027] As a preferred solution, the raw material I also includes 15 to 30 parts of water.
[0028] The present invention also provides a method for preparing a semi-internal combustion solid waste-based ceramic flat membrane, which comprises the following steps:
[0029] 1) After the raw materials I are mixed, aging, extrusion molding, drying and sintering I are performed in sequence to obtain a support body;
[0030] 2) The raw material II is wet-milled, sprayed onto the surface of the support, and then sintered II to obtain a ceramic membrane.
[0031] As a preferred solution, the aging conditions are: temperature of 20-25°C, humidity of 50±10rh%, and time of 24-36h.
[0032] As a preferred solution, the drying condition is: drying at 160-180° C. for 1-3 hours by microwave drying. Microwave drying can ensure that the drying rate inside and outside the green body is consistent, and the generation of cracks is suppressed.
[0033] As a preferred solution, the sintering conditions I are: temperature of 1150-1200° C. and time of 1.5-2.5 hours.
[0034] As a preferred solution, the spraying conditions are: the spraying pressure is 0.35-0.5 MPa, the number of spray layers is 2-3 layers, and the total spraying thickness is 15-20 μm.
[0035] As a preferred solution, the conditions of sintering II are: temperature of 1050-1100° C. and time of 1.5-2.5 hours.
[0036] The method for preparing the support of the ceramic flat membrane of the present invention comprises the following steps:
[0037] 1) After weighing the powder in raw material I according to the proportion, use an inclined countercurrent mixer to mix evenly for 20 to 25 minutes;
[0038] 2) Weigh the liquid material in raw material I according to the proportion, adjust the temperature of purified water to 60-80° C., and stir for 30 minutes to allow the release agent to fully dissolve and the various organic substances to be fully mixed;
[0039] 3) Pour the mixed liquid into the mixer at a uniform speed and continue mixing for 5 to 10 minutes;
[0040] 4) Place the mixed clay in a constant temperature and humidity environment at 20-25°C and 50±10rh% for 24-36 hours to age;
[0041] 5) The aged mud is kneaded by a high-pressure vacuum extruder and extruded to form a fly ash ceramic membrane support body, and the body is dried in a microwave drying furnace at 160-180° C. for 1-3 hours;
[0042] 6) Sintering the green body at 1150-1200° C. for 1.5-2.5 hours to obtain a ceramic flat membrane support.
[0043] The pore size of the prepared ceramic flat membrane support is 1.5-2 μm, the bending strength is 25-35 MPa, and the pure water flux is 2-3 m 3 / m 2 ·h, acid and alkali corrosion strength 20~25MPa.
[0044] The method for preparing the separation membrane layer of the ceramic flat membrane of the present invention comprises the following steps:
[0045] 1) Mix fly ash powder, nano-alumina powder, high-temperature binder and dispersant by weight, add water, and mix by fast ball mill to obtain film slurry; the high-temperature binder includes 6 to 12 parts of borax, 2 to 5 parts of magnesium oxide, 4 to 8 parts of zinc oxide, and 20 to 35 parts of albite by weight;
[0046] 2) Spraying the membrane layer slurry onto the surface of the support body at a spraying pressure of 0.35-0.5 MPa, 2-3 times of spraying, a thickness of 15-20 μm, and performing infrared drying after spraying; the membrane layer slurry is evenly and quickly covered on the surface of the substrate through the spraying process, so that the pore structure of the produced ceramic flat membrane is stable and can achieve the expected filtering effect.
[0047] 3) Sintering treatment: the sintering temperature is 1050-1100°C and the time is 1.5-2.5 hours.
[0048] The pore size of the separation membrane layer in the prepared ceramic flat membrane is 150-200nm, the bending strength is 25-35MPa, and the pure water flux is 0.7-1m 3 / m 2 ·h, acid and alkali corrosion strength 20~25MPa.
[0049] Compared with the prior art, the technical solution of the present invention has the following advantages and beneficial effects:
[0050] During the preparation of ceramic flat membranes, the present invention replaces the alumina raw materials in the traditional process with silicon-alumina solid waste raw materials such as fly ash or gasified slag. The performance of the ceramic flat membranes produced is equivalent to that of the ceramic flat membranes produced with traditional alumina raw materials, but the raw material cost is greatly reduced, and it has absolute market competitiveness.
[0051] The present invention adopts a special composite high-temperature coagulant in the process of preparing the ceramic flat membrane, which can greatly reduce the melting temperature of the raw materials and significantly reduce the sintering temperature of the separation membrane layer. On the one hand, it can prevent the secondary high-temperature sintering from affecting the pore structure of the support body and can better match the support body. On the other hand, the introduction of magnesium and zinc minerals can not only reduce the temperature but also improve the alkali resistance of the membrane layer.
[0052] In the process of preparing the ceramic flat membrane, the present invention adds coal gangue with relatively high calorific value to the raw material of the support body, so that internal combustion and external burning can be achieved in the production process, which significantly reduces the roasting energy consumption and effectively reduces the sintering cost. As an internal combustion material, coal gangue is composed of SiO 2 As the main component, it can be used directly as a raw material, but the plasticity of coal gangue is poor, therefore, its addition amount should be controlled within a certain range, and the combustion and volatilization of carbon in coal gangue will play a partial role as a pore-forming agent, which can reduce the amount of pore-forming agent added in the original formula and further reduce the cost; in terms of calorific value, different grades of coal gangue or coal slime, gasified slag have a calorific value of 500 to 1500 kcal per kilogram. According to the different calorific values and in order to maximize the use of fly ash, the addition amount of coal gangue is 5 to 15wt%. Calculated based on the received low calorific value of coal gangue of 1000Kcal / kg, the total calorific value of coal gangue added to every 10,000 square meters of ceramic membrane is 7500000Kcal, which is equivalent to 1071kg of standard coal and 882 cubic meters of natural gas based on the calorific value of 7000Kcal / kg per kilogram of standard coal. The energy consumption of roasting each flat membrane is reduced by 5.2% compared with the flat membrane fired in traditional roller kiln. Coal gangue also contains a large amount of alkaline oxide components, which can be used as a sintering aid to help reduce the sintering temperature.
[0053] The present invention utilizes inorganic non-metallic industrial solid wastes such as fly ash, gasification slag, and coal gangue in the process of preparing ceramic flat membranes. For example, the maximum proportion of these solid waste raw materials in the support body can reach 85%. Compared with traditional alumina flat membranes, the raw material cost alone can be reduced by 46%, and a ceramic flat membrane that can replace the traditional ceramic flat membrane can be prepared. The ceramic flat membrane can be used to filter sewage, achieving pollution control with pollution, and has great development prospects.
[0054] In the process of preparing the ceramic flat membrane of the present invention, the sintering temperature can be adjusted at 1000-1100°C according to different raw materials, the product temperature range can reach 25-40°C, and the product uniformity is well controlled. Compared with the traditional alumina flat membrane, after using this binder, the sintering temperature of the fly ash flat membrane can be reduced by 100-150°C, and up to 3,600 cubic meters of natural gas can be saved per 10,000 square meters of flat membrane, and the sintering energy consumption is reduced by about 20%. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1This is the ceramic flat membrane sample prepared in Example 1; the sample has good apparent quality and its physical properties meet the standards.
[0056] Figure 2 This is the microscopic morphology of the ceramic flat membrane sample prepared in Example 1; the sample surface has a separation membrane layer with uniform pore size distribution. From the cross section, it can be seen that the membrane layer is well bonded to the support, the membrane layer has a moderate thickness, and the separation accuracy is high. DETAILED DESCRIPTION
[0057] The following specific examples are intended to further illustrate the present invention rather than to limit the scope of protection of the claims.
[0058] The raw materials used in the following examples are all directly industrial grade commercial reagents unless otherwise specified.
[0059] The main components of fly ash used in the following examples and comparative examples are Al by weight. 2 O 3 The content is 37%, SiO 2 The content is 35%.
[0060] Example 1
[0061] Step 1: weigh the raw materials by weight, with each part weighing 10g, including 65 parts of 5.5μm fly ash, 13 parts of 3μm high calorific value gasified slag, 15 parts of 5μm alumina powder, and 8 parts of 7μm bentonite, and mix them in a countercurrent mixer for 20 minutes after weighing; weigh 6 parts of corn starch, 4 parts of hydroxypropyl cellulose, and 13 parts of 5μm phosphate glass powder, and mix them in a mixer for 5 minutes;
[0062] Step 2: Weigh 5 parts of polyethylene glycol, 1 part of sodium humate, 4 parts of 99.9% pure FAME fatty acid methyl ester, 2 parts of glycerol, 0.4 parts of 400 type stearic acid, and 22 parts of 65°C purified water by weight, stir for 30 minutes, then pour into a mixer and continue mixing for 8 minutes;
[0063] Step 3: Place the evenly mixed mud in a constant temperature and humidity environment at 25°C and 60rh% for aging for 30 hours. The aged mud is kneaded twice using a high-pressure vacuum extruder and extruded to form a fly ash ceramic membrane support body. The body is dried at 160°C for 2 hours in a microwave drying furnace, and then sintered at 1160°C for 2 hours in a muffle furnace. After natural cooling, it is taken out for use, as shown in Performance Table 1.
[0064] Step 4: weigh the raw materials by weight, with each part weighing 10g, weigh 10 parts of borax, 4 parts of magnesium oxide, 5 parts of zinc oxide, and 25 parts of albite, use a fast mill to grind and mix for 10 minutes to 1μm to prepare a high-temperature binder; weigh 40 parts of 0.7μm fly ash, 40 parts of 0.6μm alumina powder, 0.2 parts of sodium acrylate, 4 parts of high-temperature binder, and 250 parts of water, add them to a ball mill and wet grind and mix for 3h, then adjust the spray gun air pressure to 0.44MPa, spray 2 layers, after infrared drying, use a muffle furnace to sinter at 1070℃ for 2h, cool naturally and take out for inspection, as shown in Performance Table 1.
[0065] Example 2
[0066] Step 1: weigh the raw materials by weight, with each part weighing 10g, including 55 parts of 5.5μm fly ash, 8 parts of 2μm high calorific value coal gangue, 9 parts of 5μm alumina powder, and 4 parts of 7μm Suzhou soil, and mix them in a countercurrent mixer for 25 minutes after weighing; weigh 5 parts of corn starch, 4 parts of hydroxypropyl cellulose, and 10 parts of 5μm borate glass powder, and mix them in the mixer for 5 minutes;
[0067] Step 2: Weigh 4.5 parts of polyethylene glycol, 0.8 parts of tanning water reducer, 5 parts of 99.9% pure FAME fatty acid methyl ester, 2 parts of glycerol, 0.3 parts of emulsified silicone oil, and 20 parts of 65°C purified water by weight, stir for 30 minutes, then pour into a mixer and continue mixing for 7 minutes;
[0068] Step 3: Place the evenly mixed mud in a constant temperature and humidity environment at 25°C and 60rh% for aging for 24 hours. The aged mud is kneaded twice using a high-pressure vacuum extruder and extruded to form a fly ash ceramic membrane support body. The body is dried at 165°C for 2 hours in a microwave drying furnace, and then sintered at 1150°C for 2 hours in a muffle furnace. After natural cooling, it is taken out for use, as shown in Performance Table 1.
[0069] Step 4: weigh the raw materials by weight, with each part weighing 10g, weigh 8 parts of borax, 3 parts of magnesium oxide, 4 parts of zinc oxide, and 30 parts of albite, use a fast mill to grind and mix for 10 minutes to 1μm to prepare a high-temperature binder; weigh 30 parts of 0.75μm fly ash, 45 parts of 0.6μm alumina powder, 0.15 parts of sodium acrylate, 5 parts of high-temperature binder, and 250 parts of water, add them to a ball mill and wet grind and mix for 3h, then adjust the spray gun air pressure to 0.5MPa, spray 2 layers, after infrared drying, use a muffle furnace to sinter at 1060℃ for 2h, cool naturally and take out for inspection, as shown in Performance Table 1.
[0070] Example 3
[0071] Step 1: weigh the raw materials by weight, with each part weighing 10g, including 70 parts of 5.5μm fly ash, 15 parts of 2.5μm high calorific value coal slime, 15 parts of 5μm alumina powder, and 8 parts of 7μm ball clay, and mix them in a countercurrent mixer for 22 minutes after weighing; weigh 7 parts of corn starch, 6 parts of sodium lignin sulfonate, and 15 parts of 5μm phosphate glass powder, and mix them in a mixer for 5 minutes;
[0072] Step 2: Weigh 4.5 parts of polyethylene glycol, 0.66 parts of sodium humate, 6 parts of 99.9% pure FAME fatty acid methyl ester, 1.5 parts of glycerol, 0.6 parts of oleic acid, and 25 parts of 65°C purified water by weight, stir for 30 minutes, then pour into a mixer and continue mixing for 10 minutes;
[0073] Step 3: Place the evenly mixed mud in a constant temperature and humidity environment at 25°C and 60rh% for aging for 30 hours. The aged mud is kneaded twice using a high-pressure vacuum extruder and extruded to form a fly ash ceramic membrane support body. The body is dried at 180°C for 2 hours in a microwave drying furnace, and then sintered at 1160°C for 2 hours in a muffle furnace. After natural cooling, it is taken out for use, as shown in Performance Table 1.
[0074] Step 4: weigh the raw materials by weight, with each part weighing 10g, weigh 10 parts of borax, 3 parts of magnesium oxide, 4.5 parts of zinc oxide, and 35 parts of albite, use a fast mill to grind and mix for 10 minutes to 1μm to prepare a high-temperature binder; weigh 40 parts of 0.7μm fly ash, 30 parts of 0.6μm alumina powder, 0.15 parts of sodium acrylate, 3 parts of high-temperature binder, and 250 parts of water, add them to a ball mill and wet grind and mix for 3h, then adjust the spray gun air pressure to 0.35MPa, spray 3 layers, after infrared drying, use a muffle furnace to sinter at 1075℃ for 2h, cool naturally and take out for inspection, as shown in Performance Table 1.
[0075] Comparative Example 1
[0076] Step 1: weigh the raw materials by weight, with each part weighing 10g, including 65 parts of 5.5μm fly ash, 15 parts of 5μm alumina powder, and 8 parts of 7μm bentonite, and mix them in a countercurrent mixer for 20 minutes after weighing; weigh 6 parts of corn starch and 4 parts of hydroxypropyl cellulose, and mix them in the mixer for 5 minutes;
[0077] Step 2: Weigh 5 parts of polyethylene glycol, 1 part of sodium humate, 4 parts of 99.9% pure FAME fatty acid methyl ester, 2 parts of glycerol, 0.4 parts of 400 type stearic acid, and 22 parts of 65°C purified water by weight, stir for 30 minutes, then pour into a mixer and continue mixing for 8 minutes;
[0078] Step 3: Place the evenly mixed mud in a constant temperature and humidity environment at 25°C and 60rh% for aging for 30 hours. The aged mud is kneaded twice by a high-pressure vacuum extruder and extruded to form a fly ash ceramic membrane support body. The body is dried at 160°C for 2 hours in a microwave drying furnace; then it is sintered at 1160°C for 2 hours in a muffle furnace, and taken out after natural cooling for use, as shown in Performance Table 1.
[0079] Step 4: weigh the raw materials by weight, with each part weighing 10g, weigh 10 parts of borax, 4 parts of magnesium oxide, 5 parts of zinc oxide, and 25 parts of albite, use a fast mill to grind and mix for 10 minutes to 1μm to prepare a high-temperature binder; weigh 40 parts of 0.7μm fly ash, 40 parts of 0.6μm alumina powder, 0.2 parts of sodium acrylate, 4 parts of high-temperature binder, and 250 parts of water, add them to a ball mill and wet grind and mix for 3h, adjust the spray gun air pressure to 0.44MPa, spray 2 layers, after infrared drying, use a muffle furnace to sinter at 1070℃ for 2h, cool naturally and take out for inspection, as shown in Performance Table 1.
[0080] Comparative Example 2
[0081] Step 1: weigh the raw materials by weight, with each part weighing 10g, including 55 parts of 5.5μm fly ash, 8 parts of 2μm high calorific value coal gangue, 9 parts of 5μm alumina powder, and 4 parts of 7μm Suzhou soil, and mix them in a countercurrent mixer for 25 minutes after weighing; weigh 5 parts of corn starch, 4 parts of hydroxypropyl cellulose, and 10 parts of 5μm borate glass powder, and mix them in the mixer for 5 minutes;
[0082] Step 2: Weigh 4.5 parts of polyethylene glycol, 0.8 parts of tanning water reducer, 99.9% pure FAME fatty acid methyl ester, 2 parts of glycerol, 0.3 parts of emulsified silicone oil, and 20 parts of 65°C purified water by weight, stir for 30 minutes, then pour into a mixer and continue mixing for 7 minutes;
[0083] Step 3: Place the evenly mixed mud in a constant temperature and humidity environment at 25°C and 60rh% for aging for 24 hours. The aged mud is kneaded twice using a high-pressure vacuum extruder and extruded to form a fly ash ceramic membrane support body. The body is dried at 165°C for 2 hours in a microwave drying furnace, and then sintered at 1150°C for 2 hours in a muffle furnace. After natural cooling, it is taken out for use, as shown in Performance Table 1.
[0084] Step 4: weigh the raw materials by weight, with each portion weighing 10g, and weigh 30 portions of 0.75μm fly ash, 45 portions of 0.6μm alumina powder, 0.15 portions of sodium acrylate, and 250 portions of water. Add them into a ball mill and mix them for 3 hours, then adjust the spray gun air pressure to 0.5MPa, spray 2 layers, and after infrared drying, use a muffle furnace to sinter at 1060℃ for 2h, cool naturally, and take out for testing, as shown in Performance Table 1.
[0085] Comparative Example 3
[0086] Step 1: weigh the raw materials by weight, with each part weighing 10g, including 70 parts of 5.5μm fly ash, 15 parts of 2.5μm high calorific value coal slime, and 8 parts of 7μm ball clay, and mix them in a countercurrent mixer for 22 minutes after weighing; weigh 7 parts of corn starch, 6 parts of sodium lignin sulfonate, and 15 parts of 5μm phosphate glass powder, and mix them in a mixer for 5 minutes;
[0087] Step 2: Weigh 4.5 parts of polyethylene glycol, 0.66 parts of sodium humate, 6 parts of 99.9% pure FAME fatty acid methyl ester, 1.5 parts of glycerol, 0.6 parts of oleic acid, and 25 parts of 65°C purified water by weight, stir for 30 minutes, then pour into a mixer and continue mixing for 10 minutes;
[0088] Step 3: Place the evenly mixed mud in a constant temperature and humidity environment at 25°C and 60rh% for aging for 30 hours. The aged mud is kneaded twice using a high-pressure vacuum extruder and extruded to form a fly ash ceramic membrane support body. The body is dried at 180°C for 2 hours in a microwave drying furnace, and then sintered at 1160°C for 2 hours in a muffle furnace. After natural cooling, it is taken out for use, as shown in Performance Table 1.
[0089] Step 4: weigh the raw materials by weight, with each part weighing 10g, weigh 10 parts of borax, 3 parts of magnesium oxide, 4.5 parts of zinc oxide, and 35 parts of albite, use a fast mill to grind and mix for 10 minutes to 1μm to prepare a high-temperature binder; weigh 40 parts of 0.7-micron fly ash, 30 parts of 0.6μm alumina powder, 0.15 parts of sodium acrylate, 3 parts of high-temperature binder, and 250 parts of water, add them to a ball mill and wet grind and mix for 3 hours, then adjust the spray gun air pressure to 0.35MPa, spray 3 layers, after infrared drying, use a muffle furnace to sinter at 1075℃ for 2 hours, and take out for inspection after natural cooling, as shown in Performance Table 1.
[0090] Table 1 Comparison of the performance of solid waste-based ceramic flat membranes prepared in Examples 1 to 3 and Comparative Examples 1 to 3
[0091]
[0092]
Claims
1. A semi-internal combustion solid waste-based ceramic flat membrane, characterized in that: The invention comprises a support and a separation membrane layer on the surface thereof; the support is obtained by extrusion molding and sintering of a raw material I including silicon aluminum solid waste raw materials, micron-sized aluminum oxide powder and an internal combustion agent; the separation membrane layer is obtained by spray molding and sintering of a raw material II including fly ash, nano-sized aluminum oxide powder and a high-temperature binder; The high temperature binder is composed of the following components by weight: 6-12 parts of borax, 2-5 parts of magnesium oxide, 4-8 parts of zinc oxide, and 20-35 parts of albite; The raw material II comprises the following components in parts by weight: 30-40 parts of fly ash, 40-50 parts of nano-alumina powder, 3-8 parts of high-temperature binder, and 0.1-0.5 parts of dispersant.
2. A semi-internal combustion solid waste-based ceramic flat membrane according to claim 1, characterized in that: The particle size of the fly ash is 0.6-0.85 μm; The particle size of the nano-alumina powder is 0.6-0.7 μm; The particle size of the high temperature binder is 0.8-1 μm.
3. A semi-internal combustion solid waste-based ceramic flat membrane according to claim 1, characterized in that: The raw material I comprises the following components in parts by weight: 55-70 parts of silicon aluminum solid waste raw materials, 5-15 parts of internal combustion agent, 7-15 parts of micron-sized alumina powder, 1-8 parts of plastic clay, 4-7 parts of pore-forming agent, 2-6 parts of temporary binder, 10-15 parts of low-melting point glass powder, 3-7 parts of plasticizer, 0.5-2.5 parts of water reducer, 3-8 parts of lubricant, 1-2 parts of water retaining agent, and 0.2-1 parts of release agent.
4. A semi-internal combustion solid waste-based ceramic flat membrane according to claim 3, characterized in that: The silicon-aluminum solid waste raw material includes at least one of fly ash bottom ash, fly ash fly ash, gasification slag coarse slag, and gasification slag fine slag; The particle size of the silicon-aluminum solid waste raw material is 5-6.5 μm, the aluminum content is ≥25wt%, and the silicon content is ≥35wt%; The internal combustion agent includes at least one of coal gangue, coal slime, and high calorific value gasified slag; The particle size of the internal combustion agent is 2-3 μm, and the received low calorific value is 600-1200 Kcal / kg; The low-melting-point glass powder includes at least one of silicate glass powder, borate glass powder, and phosphate glass powder; the softening and melting temperature of the low-melting-point glass powder is 800-1000° C.; The water reducing agent includes at least one of sodium humate, sodium carbonate, and tanning agent water reducing agent; The release agent includes at least one of 400 type stearic acid, oleic acid, and emulsified silicone oil.
5. The method for preparing a semi-internal combustion solid waste-based ceramic flat membrane according to any one of claims 1 to 4, characterized in that: The following steps are involved: 1) After the raw materials I are mixed, aging, extrusion molding, drying and sintering I are performed in sequence to obtain a support body; The aging conditions are: temperature of 20-25°C, humidity of 50±10rh%, and time of 24-36h; The drying conditions are: drying by microwave drying at 160-180° C. for 1-3 h; The sintering conditions are as follows: temperature of 1150-1200°C and time of 1.5-2.5 hours. 2) The raw material II is wet-milled and then sprayed onto the surface of the support body, and then sintered II to obtain a solid waste-based ceramic flat membrane.
6. The method for preparing a semi-internal combustion solid waste-based ceramic flat membrane according to claim 5, characterized in that: The spraying conditions are as follows: the spraying pressure is 0.35-0.5 MPa, the number of spray layers is 2-3 layers, and the total spraying thickness is 15-20 μm.
7. The method for preparing a semi-internal combustion solid waste-based ceramic flat membrane according to claim 5, characterized in that: The conditions of sintering II are: temperature of 1050-1100° C. and time of 1.5-2.5 hours.
Citation Information
Patent Citations
Ceramic flat membrane for sewage treatment and preparation method of ceramic flat membrane
CN108246119A
Process for preparing high-performance ceramic plate film supporting body
CN109851328A
Preparation method of coal ash-aluminum oxide double-layer composite micro-filtration membrane
CN109126482A
High-flux ceramic flat sheet membrane and preparation method thereof
CN110256059A